PERCEPTION AND EXPERIENCE OF MENTOR TEACHERS TOWARD ENGLISH EDUCATION STUDY PROGRAM STUDENTS UNDERTAKING TEACHING PRACTICE 2 (PLP II) - Bustam, Derry Ellis Novela; Susyla, Dian; Angraini, Ria (Jurnal Review Pendidikan dan Pengajaran, 2024)
This research is based on the assessment of PLP 2 implementation activities at Bengkulu Muhammadiyah University which only assesses student teaching competencies. at this time the role of a teacher is not only to be a teaching staff who has good competence, but teachers must have professional teacher traits that are ethical, disciplined and responsible. This study aims to find out how do the perceptions and experiences of student teachers towards english language study programme students who carry out PLP 2. the purpose of this study is to find out how the perceptions and experiences of student teachers towards english language study programme students who carry out PLP 2 are. the purpose of this research is to find out how the perceptions and experiences of student teachers towards students who carry out PLP 2. the results of this research are input to the english education study programme to improve and improve the abilities of students who will carry out PLP 2 in the next semester. the results of this research show that the student teachers are satisfied with the performance of students who carry out PLP 2. the criteria for this performance include the ability to design and implement lessons, ethics and discipline, and responsibility for the tasks assigned during the implementation of activities.